Impacto da geração fotovoltaica nas receitas da distribuidora considerando a vida útil dos transformadores - Bruno Randazzo Baroni (2020)
Regulatory policies in favor of greater use of renewable energy sources, together with a significant increase of new facilities, drive a growing integration of distributed generation (DG) in distribution networks. For regulators to promote integration of DG in accordance with policy objectives, the impact of DG on different distribution costs must be identified and analyzed quantitatively. GD affects the planning and operation of the distribution network and, consequently, network costs may be higher or lower compared to a traditional network scenario. This thesis evaluates the effect of photovoltaic (PV) generation, with and without energy storage, on the aging of overhead distribution transformers and on the allowed revenue of utilities that defines tariff readjustments. A methodology based on the calculation of the depreciation rate of assets and replacement of transformers as a function of transformers’ aging is proposed. Different penetration levels of PV generation are considered by means of a probabilistic load flow using the Monte Carlo simulation method: load randomness, solar irradiation, location of the PV systems and ambient temperature are modeled. Three indexes are defined to represent the effects and lead the discussion. The network hosting capacity is analyzed in relation to overvoltage and overcurrent impacts. A real case study based on representative feeders of a distribution utility in the Southeast of Brazil is conducted by computer simulations. Results indicate that the effect of PV generation without energy storage increases revenue readjustments when penetration is over 30%. PV systems with storage reduce revenue readjustments in relation to the basic scenario. Overvoltages may limit PV generation at high penetration levels, overcurrents not being a major problem.